The paranoid apocalypse: a hundred-year retrospective on the Protocols of the elders of Zion - Landes, Richard Allen; Katz, Steven T. (Elie Wiesel Center for Judaic Studies series, 2012)
Pt. 1. Conceptual prelude -- pt. 2. Medieval prologue -- pt. 3. The early years -- pt. 4. Post-Holocaust protocals : non-western variations -- pt. 5. Protocals at the turn of the millennium : the return of the repressed -- pt. 6. Quo vadis?